Come Live the Good Life: A Rhetorical Examination of the Persuasive Techniques on the New Zealand Immigration Service Website - Kalinowski, Abigail Fonseca (Auckland University of Technology, 2013)
This research study sought to analyse key web-pages on the New Zealand Immigration Service (NZIS) website so as to understand what persuasive techniques were being employed by the text, in an attempt to appeal to potential migrants. New Zealand is a country that looks to immigration to assist in its population growth and economic development. Attracting potential migrants to our shores (when they have the option to migrate to Australia other countries) is vital. Two of Sonja Foss’s (2004) approaches to rhetorical criticism were used, namely, the narrative approach and the metaphor approach. Text was analysed to explore both its dimensions and explanation. Examining the text’s dimensions allowed for the exploration of design features such as sentence structure and tone, while exploring the explanation of narrative assisted in the analysis of what the text was trying to communicate and how it was doing so. Foss’s metaphor approach was used to analyse the images and colours present on the web-pages so as to discover their metaphoric meaning and to understand how their inclusion either supported or disagreed with the persuasive messages put forth by the text. The findings of this thesis indicated that the key persuasive messages communicated by text, images and colour centred on several themes. The first theme was concerned with conveying a sense of informality and friendliness as key characteristics of the NZIS website, and by association its representatives as well. The second theme focused on communicating messages about New Zealand’s natural beauty – the message of a "clean, green New Zealand” is still an important persuasive message being promoted overseas. The image of a “clean, green New Zealand” is also complemented by a message that focuses on New Zealand’s outdoor lifestyle. The third theme focused on the presentation of people of different ethnicities on the NZIS website, as a method of either pointing to their inclusion in New Zealand society already or reflecting the NZIS’s intention to attract migrants from these ethnicities. The use of colour appeared to support the above assertions, particularly with regard to promoting New Zealand’s natural diversity and also as a design and style feature. Limitations of the research study included the fact that only four web-pages were analysed as part of this research study, as the time-frame did not allow for an analysis of the entire NZIS website. These web-pages were chosen because they offered the best chance of yielding rich findings, after applying Foss’s two approaches to rhetorical analysis to their text. This research study would also have benefited from primary research conducted on the effect of text on readers if the NZIS website would have allowed for a comparison of migrants experiences of text on the NZIS website and their real life experiences. This is potentially an area for future research. In addition to this, an analysis of “plain English” and its effect on sentence composition is another area of future research.
Keywords: Rhetorical analysis; Immigration; Persuasion